ACADEMIC WRITING NEEDS OF POSTGRADUATE RESEARCH STUDENTS IN MALAYSIA - Joanna Joseph Jeyaraj (UUM Press, 2020)
Purpose â€" In this study, the writing needs of postgraduate research students are explored, so that support structures that enable successful completion rates and student satisfaction can be identified. Postgraduate education is expanding in Malaysian public and private higher education institutions; yet research tends to focus on public institutions, because private institutions have traditionally been oriented towards teaching instead of research. Therefore, this study explores the needs of students in a branch campus of a private overseas university in Malaysia.   Methodology - Semi-structured exploratory interviews were carried out with six postgraduate students, so that a deeper understanding of their research writing needs could be obtained. Interviews were then analysed using a general inductive approach.   Findings â€" It was found that students required support in three main areas: writing, supervision and ICT. Students sought English language support and more workshops and programmes which specifically dealt with thesis writing. They also believed that peer support groups would be beneficial. Secondly, more guidance was needed from supervisors to enable greater clarity on writing and institutional processes and procedures. Finally, students wanted greater access to ICT writing tools to facilitate writing and language learning.   Significance â€" The findings of this study are beneficial to institutions seeking to provide greater support for postgraduate students to ensure timely completion rates and greater student satisfaction. Based on the findings of this study, it is recommended that postgraduate support incorporate 3Ps, i.e., be pedagogically driven; peer oriented; and programmatically implemented.